2018
DOI: 10.1002/anie.201809463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Conformation‐Dependent Mechanoluminescence: Same Mechanical Stimulus but Different Emissive Color over Time

Abstract: A phenothiazine derivative of FCO-CzS with changeable mechanoluminescence is reported, which, upon continuous mechanical stimulus, shows mechanoluminescent emission from blue to white and yellow. Careful analysis of the experimental results, coupled with the well-understood photoluminescence theory, show that the molecular conformation transition of the phenothiazine group from quasi-axial to quasi-equatorial is responsible for this dynamic mechanoluminescence effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(116 citation statements)
references
References 46 publications
1
112
0
2
Order By: Relevance
“…As mentioned above (Section3), Bryce and co-workerse legantly revealed that D-A compound OPM (Figure 25 a), which adopted aq uasi-axial conformation in the single-crystal state, emitted RTP (Figure 25 b), whereas its regioisomer OMP (Figure 25 a), which adopted aq uasi-equatorial conformation, exclusivelyi rradiated TADF (Figure 25 c). [72] Given this report,i t was speculated that the observation of am echano-induced emission-color change in FCO-CzS,a sd isclosed by the Li group, [100] could correspond to an emission change from RTP to TADF as ar esult of ac onformational change from quasiaxial to quasi-equatorial. [98].SC 2 = 9,9'-(sulfonylbis ([1,1'-biphenyl]-4',4diyl))bis(9H-carbazole), SP 2 = 10,10'-(sulfonylbis(4,1-phenylene))bis(10H-phenothiazine).…”
Section: Tadf-active White-light-emitting (Dual-emitting) Materials Tmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned above (Section3), Bryce and co-workerse legantly revealed that D-A compound OPM (Figure 25 a), which adopted aq uasi-axial conformation in the single-crystal state, emitted RTP (Figure 25 b), whereas its regioisomer OMP (Figure 25 a), which adopted aq uasi-equatorial conformation, exclusivelyi rradiated TADF (Figure 25 c). [72] Given this report,i t was speculated that the observation of am echano-induced emission-color change in FCO-CzS,a sd isclosed by the Li group, [100] could correspond to an emission change from RTP to TADF as ar esult of ac onformational change from quasiaxial to quasi-equatorial. [98].SC 2 = 9,9'-(sulfonylbis ([1,1'-biphenyl]-4',4diyl))bis(9H-carbazole), SP 2 = 10,10'-(sulfonylbis(4,1-phenylene))bis(10H-phenothiazine).…”
Section: Tadf-active White-light-emitting (Dual-emitting) Materials Tmentioning
confidence: 96%
“…In 2018, Li and co-workersr eported that am echanoluminescence (ML)-active D-A compound, FCO-CzS,s howed as imilar mechano-induced ratiometric emission-color change (Figure 24 a). [100] Upon grinding crystals of PCO-CzS,t he emission color changed fromb lue (l em = 434 nm, prompt fluorescence) to light yellow (l em = 434 and 544 nm, prompt fluorescence and delayed fluorescence; Figure24b). The authors ascribed this dramatic changeine mission profile to variationi nt he irradiative pathway (PF to delayed fluorescence) asi nduced by a conformational change in the phenothiazine unit.…”
Section: Tadf-active White-light-emitting (Dual-emitting) Materials Tmentioning
confidence: 99%
“…For instance, the carbon precursor used in this study (namely, trimellitic acid) shows such RTP properties (Supporting Information, Figure S19). Therefore, the achievement of grinding‐tolerant (or amorphous) metal‐free RTP materials is very challenging, but highly desirable . Interestingly, the TA‐CDs that were prepared in this study display nearly constant RTP intensity under continuously grinding (Figure a).…”
Section: Resultsmentioning
confidence: 89%
“…The functional groups on the TPE core also play ac rucial role in regulating their stimuli-responsiveb ehavior.I na ddition to the above-discussedd ifferences in their fluorescence, mechanochromism,a nd self-assembly properties, the (Z)-TPE and (E)-TPE isomers have also shown different triboluminescence (TL) properties. [75][76][77] Recently,T ue tal. studied crystals of the previous reportedlyf luorine-and methoxy-substituted TPE, (Z)-/(E)-TPE-FM ( Figure 15 a).…”
Section: Mechanoluminescence Propertiesoft He Z/e Isomersmentioning
confidence: 99%